Project Report on Analysis of Waste Water Characteristics - RAGAVAN K, SENTHIL VADIVU T A, MANTHAIAN K, SUGUMAR K, KARUPPA SAMY G, and SENTHIL KUMAR V (1991)
INTERNAL GUIDE:RANGANATHAN B A,MVJCE
Keywords: Analysis of Waste Water Characteristics